Scientific and Regulatory Policy Committee Points to Consider: Integration of Clinical Pathology Data With Anatomic Pathology Data in Nonclinical Toxicology Studies. (17th August 2022) - Siska, William; Schultze, Albert Eric; Ennulat, Daniela; Biddle, Kathleen; Logan, Michael; Adedeji, Adeyemi O.; Arndt, Tara; Aulbach, Adam
Abstract: Integrating clinical pathology data with anatomic pathology data is a common practice when reporting findings in the context of nonclinical toxicity studies and aids in understanding and communicating the nonclinical safety profile of test articles in development. Appropriate pathology data integration requires knowledge of analyte and tissue biology, species differences, methods of specimen acquisition and analysis, study procedures, and an understanding of the potential causes and effects of a variety of pathophysiologic processes. Neglecting these factors can lead to inappropriate data integration or a missed opportunity to enhance understanding and communication of observed changes. In such cases, nonclinical safety information relevant to human safety risk assessment may be misrepresented or misunderstood. This "Points to Consider" manuscript presents general concepts regarding pathology data integration in nonclinical studies, considerations for avoiding potential oversights and errors in data integration, and focused discussion on topics relevant to data integration for several key organ systems, including liver, kidney, and cardiovascular systems.